Gut–Brain Interactions and Their Impact on Astrocytes in the Context of Multiple Sclerosis and Beyond - Zißler, Julia; Rothhammer, Veit; Linnerbauer, Mathias (Cells, 2024)
Multiple Sclerosis (MS) is a chronic autoimmune inflammatory disease of the central nervous system (CNS) that leads to physical and cognitive impairment in young adults. The increasing prevalence of MS underscores the critical need for innovative therapeutic approaches. Recent advances in neuroimmunology have highlighted the significant role of the gut microbiome in MS pathology, unveiling distinct alterations in patients’ gut microbiota. Dysbiosis not only impacts gut-intrinsic processes but also influences the production of bacterial metabolites and hormones, which can regulate processes in remote tissues, such as the CNS. Central to this paradigm is the gut–brain axis, a bidirectional communication network linking the gastrointestinal tract to the brain and spinal cord. Via specific routes, bacterial metabolites and hormones can influence CNS-resident cells and processes both directly and indirectly. Exploiting this axis, novel therapeutic interventions, including pro- and prebiotic treatments, have emerged as promising avenues with the aim of mitigating the severity of MS. This review delves into the complex interplay between the gut microbiome and the brain in the context of MS, summarizing current knowledge on the key signals of cross-organ crosstalk, routes of communication, and potential therapeutic relevance of the gut microbiome. Moreover, this review places particular emphasis on elucidating the influence of these interactions on astrocyte functions within the CNS, offering insights into their role in MS pathophysiology and potential therapeutic interventions.
CRIS-Team Scopus Importer:2024-04-05
Keywords: dysbiosis; gut–brain interactions; microbiome; multiple sclerosis; neuroinflammation